(untitled) (Journal of actual problems of jurisprudence, 2018)
The article examines the legal nature of mediation in criminal proceedings the Republic of Kazakhstan. The brief historical analysis of the emergence of mediation. Formed a legal framework for the implementation and development of the institution of mediation in the Republic of Kazakhstan. Despite this, according to statistics almost does not develop criminal mediation at the pre-trial stage of the criminal process. In this regard, the authors propose to the Criminal Procedure Code provision on the duties of the agency conducting the criminal proceedings, to create conditions for the reconciliation of the parties, in cases prescribed by law, including by way of mediation. Key words: mediation, criminal procedure, the mediator, prosecution, judicial mediation, conciliation.